Postoperative acute pancreatitis is a serious but rare complication after distal pancreatectomy. Issue 9 (September 2021) - Loos, Martin; Strobel, Oliver; Mehrabi, Arianeb; Mihaljevic, André L.; Ramouz, Ali; Dietrich, Maximilian; Müller-Stich, Beat P.; Diener, Markus K.; Schneider, Martin; Berchtold, Christoph; Al-Saeedi, Mohammed; Feisst, Manuel; et al.
Abstract: Background: The clinical relevance of hyperamylasemia after distal pancreatectomy (DP) remains unclear and no internationally accepted definition of postoperative acute pancreatitis (POAP) exists. The aim of this study was to characterize POAP after DP and to assess the role of serum amylase (SA) in POAP. Methods: Outcomes of 641 patients who had undergone DP between 2015 and 2019 were analyzed. Postoperative SA was determined in all patients. POAP was defined based on contrast-enhanced computed tomography (CT) or intraoperative findings during relaparotomy. Results: An elevation of SA on postoperative day 1 (hyperamylasemia POD1 ) was found in 398 patients (62.1%). Twelve patients (1.87%) were identified with POAP. Ten patients demonstrated radiologic criteria for POAP and in two patients POAP was diagnosed during relaparotomy. Outcome of POAP patients was worse than that of patients with hyperamylasemia POD1 alone and that with normal SA POD1 without POAP evidence (postoperative pancreatic fistula 50% vs 30.6% vs 18.5%; length of hospital stay 26 days vs 12 vs 11, respectively). The overall 90-day mortality of all 641 patients was 0.6%. Conclusion: POAP is a serious but rare complication after DP. Hyperamylasemia POD1 is of prognostic relevance after DP, but it seems not sufficient as a single parameter to diagnose POAP.